1982
DOI: 10.1080/00480169.1982.34879
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukaemia virus infection in New Zealand cattle

Abstract: Bovine Leukaemia Virus (BLV) infection in New Zealand cattle was investigated. In a national survey of 5000 sera from 500 herds, BLV antibody was not detected. An additional 1062 sera from 140 herds were tested and 3 sera were positive. In the herd of origin of one of these 3 sera, 22.6% of cattle were serologically positive for BLV. Where cases of bovine lymphosarcoma had been diagnosed, 38 of 39 herds tested were negative for BLV antibody. Within the remaining herd, 36% of cows tested were serologically-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Bovine leukaemia virus has been found in New Zealand herds, although the prevalence of infection was low (Parrish et al, 1981). The virus has been found in meat and unpasteurized milk in other countries (Ferrer et al, 1981;Miller and Van der Maaten, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine leukaemia virus has been found in New Zealand herds, although the prevalence of infection was low (Parrish et al, 1981). The virus has been found in meat and unpasteurized milk in other countries (Ferrer et al, 1981;Miller and Van der Maaten, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic evidence for the role of zoonotic viruses in human cancer is currently weak, although some studies have found associations between various hematologic malignancies and farming (40). One candidate, bovine leukemia virus, is an exogenous C type retrovirus which has been established as the etiologic agent of the adult form of bo vine lymphosarcoma (l6) and occurs in New Zealand (42). The virus is related closely to human T-cell leukemia-lymphoma virus type I, the cause of adult T-cell leukemia in humans (43), and is transmitted horizontally (44).…”
Section: Discussionmentioning
confidence: 99%